584. Ventricular assist device infections with Pseudomonas aeruginosa. (31st December 2020) - Roberts, Scott C; Nam, Hannah H; Kumar, Rebecca N; Zembower, Teresa; Qi, Chao; Malczynski, Michael; Rich, Jonathan D; Pawale, Amit A; Harap, Rebecca S; Stosor, Valentina
Abstract: Background: Infection is a leading cause of morbidity and mortality in ventricular assist device (VAD) recipients. Pseudomonas aeruginosa (PA) is the second most common organism implicated in VAD infections, occurring in 10–50% of infections. The epidemiology of VAD recipients with PA infection are poorly described. Methods: We identified patients (pts) at Northwestern Memorial Hospital with a VAD-specific PA infection from January 1, 2012 to Dec 31, 2019. VADs included the Heartmate II, Heartmate 3, and Heartware HVAD devices. VAD-specific infections were defined according to the 2013 ISHLT Guidelines. Results: Seventeen out of 91 (18.7%) VAD infections were due to PA. Infections of the driveline exit site (DLES) occurred most commonly (n=15, 88.2%), followed by pocket (n=2, 11.8%) and pump (n=2, 11.8%) infections. Median time to infection after VAD implantation was 295 days (IQR 154 – 440 days). Eight (47.1%) pt isolates were not fluoroquinolone (FQ) susceptible. Resistance to multiple antibiotic classes was observed in pts in whom serial cultures were obtained. Median antibiotic treatment was 107 days (IQR 55 – 183 days, maximum 775 days). Five (29.4%) pts received FQ monotherapy on initial diagnosis, 3 (60%) of whom required change to a different class for resistance. Surgical debridement and VAD exchange were performed in 5 (29.4%) and 3 (17.6%) pts respectively. Co-pathogens were identified in 9 (52.9%) pts, the most common being Staphylococcus aureus (n=2) and Enterococcus spp (n=2). A total of 5 (29.4%) pts went on to successful heart transplantation; one had recurrent PA infection at the prior DLES requiring prolonged antibiotics and removal of retained DL material. All cause 1-year mortality rate was 11.7% (n = 2), both of whom died from cerebrovascular accidents. Conclusion: VAD-specific infections with PA occurred late after device implantation and required prolonged antibiotic courses. Antimicrobial resistance was high at diagnosis and worsened in pts on prolonged therapy. Morbidity and mortality in pts with PA VAD infections were high. The preponderance of DLES infections warrants further study and highlights the need for improvements in DLES care and infection prevention strategies. Disclosures: All Authors : No reported disclosures